Knowledge, attitude, and utilization of traditional medicine within the plural medical system in West Java, Indonesia - Raden Maya Febriyanti; Kurniawan Saefullah; Raini Diah Susanti; Keri Lestari (BMC, 2024)
Abstract Background The concept of 'medical pluralism' has become more popular among scholars in applied health science and prevalent in societies where one medical system alone cannot adequately meet the health care needs of the entire population. Methods The data collection is focused on the knowledge-belief-practice and the utilization of three medical systems in Kabupaten Bandung, West Java, Indonesia. Participants were purposively selected from households with at least one member experienced one of the listed diseases in the questionnaire. The extensive survey using a structured questionnaire has been undertaken to collect data on people's health care utilization behaviour. The dataset is further analyzed using multivariate analysis through non-canonical correlation, with the analytical data provided by Statistical Package for Social Sciences (SPSS). Results With regards to the total utilization by patients, the traditional medical system presents as the dominant medical system in the research area, accounting for 59.3% (n = 419) of total utilization, followed by the modern medical system (33.0%, n = 233), and transitional medical system (7.7%, n = 54). This study identified that village category, illness, illness duration, occupation, belief in traditional medicine, knowledge of modern medicine, accessibility, cost, proximity to the medical service, and insurance have significant (χ2 = 0.000) relationship with the utilization of medical systems. The results of the multivariate analysis show that the block of the predisposing socio-demographic factors and the block of the predisposing psycho-social factors correlate strongly with the utilization of medical systems. Conclusions In general, people in Kabupaten Bandung, West Java, Indonesia seeks treatment from various sources, which in the context of the medical system, consists of the traditional, transitional, and modern medical system; therefore, it adopts the patterns of transcultural health care utilization. In terms of the knowledge, beliefs, and practices of traditional medicine in West Java, the inhabitants of the five research villages were commonly familiar with medicinal plants and speak profoundly about their knowledge of traditional medicine, which in the research area is perceived as accessible, efficacious, affordable and culturally appropriate with Sundanese community.